2008
DOI: 10.1101/lm.986008
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of taste memory acquisition by experiencing previous novel taste is protein-synthesis dependent

Abstract: Very little is known about the biological and molecular mechanisms that determine the effect of previous experience on implicit learning tasks. In the present study, we first defined weak and strong taste inputs according to measurements in the behavioral paradigm known as latent inhibition of conditioned taste aversion. We then demonstrated that a strong novel taste input facilitated acquisition of the memory of subsequent weak taste input in inverse correlation with the time interval between the inputs. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 40 publications
3
54
0
Order By: Relevance
“…Local microinjection of protein synthesis inhibitor into the gustatory cortex before or just after acquisition attenuated long-but not short-term taste memory (Rosenblum et al 1993;Houpt and Berlin 1998;Merhav and Rosenblum 2008). This indicates that protein synthesis inhibitors did not affect normal neuronal function in the cortex but attenuates specifically memory consolidation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Local microinjection of protein synthesis inhibitor into the gustatory cortex before or just after acquisition attenuated long-but not short-term taste memory (Rosenblum et al 1993;Houpt and Berlin 1998;Merhav and Rosenblum 2008). This indicates that protein synthesis inhibitors did not affect normal neuronal function in the cortex but attenuates specifically memory consolidation.…”
Section: Discussionmentioning
confidence: 92%
“…We found that eEF2K ki mice showed the same natural aversion to quinine (98.4 + 0.7%, n ¼ 8) as the WT (95. In order to test the hypothesis that taste memory per se, i.e., incidental taste memory, is impaired in the ki mice, we examined the reduction in neophobia by using saccharin as a novel taste (Merhav and Rosenblum 2008). No differences in aversion index were found during four consecutive days following the first taste exposure (Fig.…”
Section: Generating Eef2k Ki Micementioning
confidence: 99%
“…2A). Like in other studies with other newborn or adult mammals (Davis and Squire 1984;Gruest et al 2004;Desgranges et al 2008;Languille et al 2008;Merhav and Rosenblum 2008) our present and previous results support the fact that the blocking effect of AN in newborn rabbits is a real amnesia and not an aversive effect (Coureaud et al 2009a. Thus, the amnesia of odorant A did not appear disruptive to the memory of odorant B. Reciprocally, 15 pups exposed to A+B, conditioned to odorant A, and reactivated with odorant B before injection of AN or saline (n ¼ 10 and 5, respectively) all responded to odorant A (x 2 , 0.1, P .…”
mentioning
confidence: 75%
“…In contrast, the latent inhibition paradigm consists of pre-exposure of the animal to a novel taste, followed by CTA, which by reducing taste neophobia allows addressing taste aversion per se. Recent studies using these behavior paradigms have demonstrated that the involvement of new protein synthesis in CTA is time limited Yefet et al 2006;Merhav and Rosenblum 2008) mTOR and taste learning…”
Section: Translation Regulation In the Cortex: The Taste Casementioning
confidence: 99%